Body over mind : 'no body, never mind' : an exegesis presented in partial fulfilment of the requirements for the degree of Master of Fine Arts at Massey University, Wellington, New Zealand - Joyce-Kellaway, Katherine May (Massey University, 2013)
My research critiques our visual and word-centric world through immersive installation environments. It explores our bodies’ sensory perceptual capabilities by creating new ways of experiencing the world through its somatic intelligence. By fabricating an environment that promotes subtle disorientations of a person[']s proprioception and simultaneously provoking a sensuous joyous response this slide between comfort and discomfort aspires to reinvigorate an old language - that of the gut. Only by being actively immersed in the work can these experiences be realized. This exegesis gives an understanding of the sources and processes in creating the work.
Keywords: Art installations; Sensory perception; Proprioception; Spatial perception; Somaesthetics; Lake Grassmere saltworks